Consequences of massive river bank erosion to the local society at Pasir Parit, Kelantan - See, Too Kay Leng; Er, Ah Choy; Mokhtar Jaafar Social, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The population living near the river basin is at risk of river bank erosion. As a consequence of hydraulics and hydrological processes, as well as floods and development activities along the river, the morphology is changing. Many ecological characteristics, including flora and fauna, human life, basin structure, and so on, may be lost as a consequence of river bank erosion. The objectives of this research are to (1) identify the impact of soil texture on river bank erosion; (2) determine the consequences of river bank erosion on the local community; and (3) propose river bank erosion mitigation strategies for the study region. We use both quantitative and qualitative approaches to analyse data in this study. An observational technique, a questionnaire survey, and a personal interview were utilised to collect data. To support our findings, we acquired secondary data from government entities (Drainage and Irrigation Department). The river bank erosion in this case study affected 17 dwellings, totalling 103 people, and two homes were consumed by the river. The impacted area of river bank erosion at the site, according to the research conclusions based on aerial photography and departmental statistical data, is roughly 120 metres in a period of 6 months. The volume of sediment lost due to bank erosion was estimated to be 360,000 cubic metres, or 1.4 hectares. As a consequence of the massive river bank erosion, the victims endured loss and worry. The following technique for preventing river bank erosion is proposed: build a concrete river cliff or gabion as soon as possible, and change the low weir so that flowing and flood water is contained in the river's main channel.